THE EFFECT OF VOCABULARY MASTERY AND GRAMMAR TOWARDS STUDENTS’ WRITING SKILL IN NARRATIVE TEXT - Ana Wiliana; Soenardjati Djajanegara (INFERENCE: Journal of English Language Teaching, 2019)
This study aims to analyze the effect simultaneously and partially of mastery of vocabulary and grammar of writing English narrative texts. The research method used is a survey with correlation and regression analysis that is by connecting data showing the mastery of vocabulary and grammar with From the result of data analysis of research, it can be concluded that: (1) there is a significant influence of mastery of vocabulary and grammar of the ability to write English narrative texts, this is proved by Sig = 0.000<0.05 and Fcount = 38.284; (2) there is a significant influence of mastery of the vocabulary of the ability to write English narrative texts, the value of Sig = 0.006 pieces of evidence this and tcount = 2.879; and (3) there is the significant influence of mastery of the grammar of the ability to write English narrative texts, this is proved by Sig = 0.000 and tcount = 4.379. Keywords: mastery of vocabulary, mastery of grammar, writing ability, English narrative text